2022
DOI: 10.3389/fmed.2022.773000
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Research Status of Neuromedin U: A Bibliometric and Visual Analysis From 1987 to 2021

Abstract: Neuromedin U (NMU) is a regulatory peptide that is widely distributed throughout the body and performs a variety of physiological functions through its corresponding receptors. In recent years, NMU has become the focus of attention in various fields of research as its diverse and essential functions have gradually been elucidated. However, there have been no bibliometrics studies on the development trend and knowledge structure of NMU research. Therefore, in this study, we used VOSviewer software to statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…EPSTI1 has also been implicated in immune response, as it promotes the expression of viral response genes and is associated with immune privilege and autoimmune diseases (79). NMU is expressed at higher levels in tumor tissues compared to normal tissues, and its expression has been associated with poor prognosis and shorter overall survival in cancer patients (80). Studies have shown that VIPR2 overexpression promotes cell proliferation in breast cancer cell lines and exacerbates tumor growth in vivo (77).…”
Section: Discussionmentioning
confidence: 99%
“…EPSTI1 has also been implicated in immune response, as it promotes the expression of viral response genes and is associated with immune privilege and autoimmune diseases (79). NMU is expressed at higher levels in tumor tissues compared to normal tissues, and its expression has been associated with poor prognosis and shorter overall survival in cancer patients (80). Studies have shown that VIPR2 overexpression promotes cell proliferation in breast cancer cell lines and exacerbates tumor growth in vivo (77).…”
Section: Discussionmentioning
confidence: 99%